Effect of Irrigation Scheduling on Moisture and Salt Distribution and Growth of Kagji Lime under Drip Irrigation in Arid Rajasthan - Beniwal, R K; Soni, M L; Yadava, N D; Prakash, Chander; Talwar, H S (Annals of Arid Zone, 2016)
A field experiment was conducted in an Aridisol on Kagji lime (Citrus aurantifolia) plants during 2001-2002 to study the effect of drip irrigation levels (Evapotranspiration coefficient (ETc) = 1.00, 0.70 ands 0.40) on spatial distribution of soil moisture, salts and plant growth. The results revealed that soil moisture decreased laterally, but increased vertically at each irrigation level. Comparatively lower soil moisture was recorded in surface soil layers during summer months. Minimum salt content was observed near the emitters and it increased laterally. Salt spreading was more in 1.00 ETc with maximum value near periphery of the wetted zone. At each lateral distance, higher salt concentration was observed at surface soil layers as compared to lower depths. Canopy diameter, number of branches and relative increase in girth were significantly affected by irrigation levels showing . minimum values at 0.40 ETc. Irrigation at 0.70 ETc levels was better over 1.00 and 0.40 in terms of increasing plant growth and saving water.